Analisa Persepsi Verifikator Terhadap Kode Tindakan Medis Di RS Umum Citra Bunda Medical Center Padang - Dewi Mardiawati; Linda Handayuni (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2021)
Based on the initial survey conducted by researchers, it was found that there were differences in perceptions between code verifiers and BPJS verifiers about medical action codes. In February, there were 15 disease codes with different perceptions, because the hospital had to follow the code based on the BPJS. The research objective was to analyze the perception of medical action codes by verifiers at Bunda Medical Center Hospital.This type of research is qualitative with a phenomonological approach. Research is conducted by in-depth interviews with 1 medical support person, 1 medical committee person, 1 code verifier, and 1 BPJS verifier, using a voice recorder and using interview guidelines. Data were analyzed using the Collaizzi method.The results showed that what hampered the implementation of the verification of medical action codes was that the doctor's writing was difficult to read by the verifier. There are differences in the perceptions of the verifier about the medical action code, where the verification of the medical action code is based on the number of resources used in the service, while the BPJS verifier thinks the medical action code is based on the level of severity or severity level. The conclusion in this study is that the educational qualifications between the BPJS verifier and the verification of medical action codes are not yet appropriate, then the BPJS verifier verifies the code based on the severity level it should be based on the most spent resources.